Phytochemical and Pharmacological potential of Amaranthus viridis L.:-A Review - Pulipati Sowjanya,; P. Srinivasa Babu,; P. Srinivasa Babu, (International Journal of Phytomedicine, 2014)
Medicinal plants are important in the traditional medicine and as well as modern pharmaceutical drugs. In traditional system of medicine various plant parts like leaves, flowers, stems, fruits, seeds, barks and even whole plants are used for the treatment. Traditionally the leaves, seeds, roots and entire plant of Amaranthus viridis Linn is used in the treatment of many diseases. Its uses include diuretic, analgesic, antipyretic, vermifuge, antiulcer antidiabetic, anti-cholesterolemic, laxative, asthma and veneral diseases. This review encompasses the available literature on Amaranthus viridis with respect to its pharmacognostic characters, physicochemical parameters, synopsis of pharmacological activities and traditional uses. This attempt provides a direction towards further research.